Pengaruh Perceived Organizational Support dan Kepuasan Kerja Sebagai Mediator Terhadap OCB Karyawan Bank X Jakarta - Ayu Merisa; Triantoro Safaria (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Competition in the world of work today is becoming tighter, particularly in the banking industry, where companies employ strategies to maintain their existence and gain acceptance from the community. An important key to maintaining and improving the quality and output of the organization is human resources. Company goals can be achieved when employees perform their tasks according to their job descriptions and are willing to take on additional responsibilities beyond their designated roles. This study aims to examine the impact of perceived organizational support and job satisfaction as mediators on organizational citizenship behavior (OCB). The research approach utilized in this study is non-experimental quantitative, employing the Structural Equation Model (SEM) technique through the AMOS program. The research type is multivariate regression analysis. For sampling, the purposive sampling technique was used, considering employees with a minimum of five years of service from the front office, general banking, and operations departments of Bank X. Data collection involved the use of scales to measure perceived organizational support, job satisfaction, and organizational citizenship behavior. The data analysis technique involved the use of Structural Equation Model (SEM) with path analysis through the AMOS program. The results demonstrated that the effect of perceived organizational support and job satisfaction on OCB, with job satisfaction as a mediator, aligns with the empirical data. Additionally, it was found that perceived organizational support has a positive and significant impact on OCB.